Knowledge and acceptance of genetically modified foodstuffs in Hungary - Bánáti, Diána; Szabó, József A. (Acta Biologica Szegediensis, 2006)
The safety evaluation of genetically modified (GM) foodstuffs is a highlighted research topic. European consumers are cautious with GM plants, their release into the environment and the consumption of GM foods. Technological changes and achievements are more and more difficult to be understood for consumers. Novel technologies and the products of the biotechnology industry are thought to bring additional risks into consumers’ life according to their perception. Consumers perceive risks on a different way than experts. 556 respondents were involved in the first survey focusing on food safety than 1000 respondents were involved in the questioning survey intending to reveal consumers’ knowledge and opinion about GM products and techniques. The opinion of consumers and professionals about gene technology is mostly negative as far as 35% of the consumers can recall more negative than positive information about GM foodstuffs and 13% can recall only negative ones. Nevertheless even if Hungarian consumers predominantly refuse GM products this proportion is still much smaller than in Western-Europe. According to 73% of the respondents it is essential to indicate the GM content on the packaging. Consumers are not sufficiently aware of the concept of biotechnology and often misunderstand it. The results reflect the insufficient information level of the Hungarian consumer and the misunderstanding of biotechnology concept.